Critical proximity in translating RRI - Anestis Amanatidis; Tom Børsen (Journal of Responsible Innovation)
The term ‘translation’ has been proliferating in reflections of researchers who participated in European projects engaging with responsible research and innovation (RRI). Additionally, the outlines of a distinct ‘translational RRI’ approach are increasingly becoming visible. Departing from the observation that RRI researchers are unavoidably implicated in this translational affair, we scrutinise the settings in which RRI travels by focusing on the interactions between ‘RRI researchers’ and ‘healthcare practitioners’ in a regional RRI project. We identify ‘critical proximity’ as a mode of RRI translation to describe the otherwise ambiguous position of RRI researchers and approximate the inherent ‘democratic qualities’ of RRI as a question of research strategy.